Students Interest and Motivation in Participating in Wrestling Extracurricular Activities in Senior High School - Bastian Tito Adiatma; Ferry Fendrian; Elzas Nurajab (Journal of Physical and Outdoor Education, 2025)
This study aims to find out the level of interest and motivation of students in participating in wrestling extracurricular activities at SMAN 1 Batujajar. Extracurricular activities are an important part of character formation and the development of students' potential, one of which is extracurricular wrestling which has physical and mental benefits. However, the low participation of students in this activity is suspected to be influenced by a lack of interest and motivation. This study uses a quantitative descriptive method with a survey approach. The population in this study is all students who participate in wrestling extracurricular as many as 30 students, and the sampling technique used is total sampling. The instrument used was a questionnaire to measure students' interest and motivation. The results of the study showed that the level of student interest in participating in wrestling extracurricular activities was in the high category, and student motivation was also relatively high. Factors that influence interest and motivation include personal interests, intrinsic drives, environmental support, and the role of coaches. These findings are expected to be material for evaluation and consideration for schools and extracurricular coaches in improving the quality of extracurricular activities, especially wrestling sports.